Molecular Tools to Identify and Characterize Malignant Catarrhal Fever Viruses (MCFV) of Ruminants and Captive Artiodactyla - Laura Bianchessi; Mara Silvia Rocchi; Madeleine Maley; Renata Piccinini; Lauretta Turin (Viruses, 2022)
The family Herpesviridae includes viruses identified in mammals, birds and reptiles. All herpesviruses share a similar structure, consisting of a large linear double-stranded DNA genome surrounded by a proteic icosahedral capsid further contained within a lipidic bilayer envelope. The continuous rise of genetic variability and the evolutionary selective pressure underlie the appearance and consolidation of novel viral strains. This applies also to several gamma(γ)-herpesviruses, whose role as primary pathogen has been often neglected and, among these to newly emerged viruses or virus variants responsible for the development of Malignant Catarrhal Fever (MCF) or MCF-like disease. The identification of γ-herpesviruses adapted to new zoological hosts requires specific molecular tools for detection and characterization. These viruses can cause MCF in livestock and wild animals, a disease generally sporadic but with serious welfare implications and which, in many cases, leads to death within a few days from the appearance of the clinical signs. In the absence of a vaccine, the first step to improve disease control is based on the improvement of molecular tools to identify and characterize these viruses, their phylogenetic relationships and evolutionary interaction with the host species. A Panherpes PCR-specific test, based on the conserved DNA polymerase gene, employing consensus/degenerate and deoxyinosine-substituted primers followed by sequencing, is still the preferred diagnostic test to confirm and characterize herpesviral infections. The drawback of this test is the amplification of a relatively short sequence, which makes phylogenetic analysis less stringent. Based on these diagnostic requirements, and with a specific focus on γ-herpesviruses, the present review aims to critically analyze the currently available methods to identify and characterize novel MCFV strains, to highlight advantages and drawbacks and to identify the gaps to be filled in order to address research priorities. Possible approaches for improving or further developing these molecular tools are also suggested.